2012
DOI: 10.1210/jc.2012-1852
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool in the Diagnosis and Follow-Up of (Cyclic) Cushing's Syndrome: Measurement of Long-Term Cortisol in Scalp Hair

Abstract: Hair samples can provide a historical timeline that corresponds with clinical course in patients with (cyclic) CS. This new diagnostic tool can contribute significantly to early recognition of patients suffering from cyclic CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 13 publications
5
97
2
2
Order By: Relevance
“…For example, HCC has been validated in conditions known to be associated with altered corstiol secretion, such as Cushing Syndrome (Manenschijn et al, 2012;Thomson et al, 2010) and pregnancy (Kirschbaum et al, 2009;Steptoe et al, 2003); HCC appears higher in chronically stressed dementia caregivers who report depressive symptoms , and has been linked with cardiovascular disease (Manenschijn et al, 2013). In the general population, in the absence of such manifest (or developing) conditions, HCC could still provide a useful biomarker of stress, but its association with perceived stress is perhaps not a useful means of validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HCC has been validated in conditions known to be associated with altered corstiol secretion, such as Cushing Syndrome (Manenschijn et al, 2012;Thomson et al, 2010) and pregnancy (Kirschbaum et al, 2009;Steptoe et al, 2003); HCC appears higher in chronically stressed dementia caregivers who report depressive symptoms , and has been linked with cardiovascular disease (Manenschijn et al, 2013). In the general population, in the absence of such manifest (or developing) conditions, HCC could still provide a useful biomarker of stress, but its association with perceived stress is perhaps not a useful means of validation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating for the potential application of HCC in clinical and epidemiological studies (Wester and van Rossum, 2015;Wosu et al, 2013) and various relationships have been demonstrated between HCC and, for example, Cushing's Syndrome (Manenschijn et al, 2012), cardiovascular disease (Manenschijn et al, 2013), depression and mood disorders (Dettenborn et al, 2012b), and anxiety (Steudte et al, 2011). However, the association between HCC and subjectively measured stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements of hair cortisol have been shown to be a sensitive biomarker of Cushing syndrome (10,14), as well as stress associated with chronic pain, myocardial infarction, congestive heat failure, and numerous other conditions (8). Changes in hair cortisol can be detected in hair within 2 mo of the corresponding changes in plasma cortisol.…”
Section: Resultsmentioning
confidence: 99%
“…Hair cortisol levels are known to be significantly elevated in patients with CS over those in the general population (sensitivity 86%, specificity 98%). 6 The advantage of using hair cortisol levels is that they can pro vide data over the previous several months in one analyti cal setting. In one study, hair samples were obtained from one lock of hair each from healthy controls, patients with CS, and patients with cyclic CS.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, hair samples were obtained from one lock of hair each from healthy controls, patients with CS, and patients with cyclic CS. 6 Cortisol measurements at 1cm intervals correspond to monthly time frames. In patients with cyclic CS, hair cortisol-level fluctuations were found to correlate with the clinical course of CS.…”
Section: Discussionmentioning
confidence: 99%